Origin and distribution of grain-coating and pore-filling chlorite in deltaic sandstones for reservoir quality assessment. (December 2021) - Griffiths, Joshua; Worden, Richard H.; Utley, James E.P.; Brostrøm, Christian; Martinius, Allard W.; Lawan, Auwalu Y.; Al-Hajri, Ali I.
Abstract: Grain-coating chlorite preserves porosity and permeability through the inhibition of quartz cement whereas pore-filling chlorite blocks pore-throats and diminishes reservoir quality. The aim of this study is to determine the origin and principal mechanisms which govern the distribution of grain-coating and pore-filling chlorite in Jurassic deltaic sandstones (Tilje Formation, Smørbukk field, Mid Norwegian Shelf). The study focussed on very high-density sampling for petrographic analysis, from three sections of sandstone core from the same well with contrasting reservoir quality, rather than the low-density sampling approach typically employed. The aim was to gain new understanding of specific controls on porosity and permeability based on core description, core analysis measurements and a suite of petrographic techniques. Results of this study show grain-coating chlorite originated from the thermally-driven recrystallisation of detrital clay coats and/or clay mineral precursors. Pore-filling chlorite has principally derived from the ductile deformation of chlorite-rich Fe-ooids, that were possibly reworked from a proximal evaporitic setting. The distribution of chlorite precursor material, detrital clay coats, and subsequently the distribution of grain-coating and pore-filling chlorite, were controlled by the relative dominance of tidal and fluvial processes active during sediment deposition. Optimum grain-coating chlorite is found in tidal-fluvial sandstones with moderate fluvial influence. Pore-filling chlorite is pervasive in tidal-fluvial channel sandstones deposited during periods of high fluvial discharge, or proximal to the central turbidity maximum zone; marked by an abundance of fluid mud. Tidal channel sandstones with no fluvial influence are pervasively quartz cemented due to an absence of grain-coating chlorite. Grain-coating chlorite and good reservoir quality occurs in heterolithic distributary mouth bar sandstones, however mixing of mud- and sand-prone facies due to intense bioturbation has reduced permeability. Results from this study can be used to predict reservoir quality in the Smørbukk field and in analogous shallow-marine sandstones worldwide. Graphical abstract: Image 1 Highlights: Chlorite has inhibited quartz cement growth in Tilje Fm (Haltenbanken, Norway) sandstones at >4, 200 m and >150 °C. High-density sampling for petrographic and petrophysical analysis was used to study grain-coating chlorite. Grain-coating and pore-filling chlorite was controlled by the relative dominance of tidal and fluvial processes. Fe-ooids and detrital Fe-rich clay supplied the ingredients that resulted in chlorite grain coats. Excess chlorite diminishes reservoir quality: it is possible to have too much chlorite in sandstone.